Justice between the young and the old - McKerlie, Dennis (Oxford : Oxford University Press, 2013)
Dennis McKerlie's monograph examines justice between age-groups with the ultimate goal of a new theory of justice that effectively grapples with questions concerning justice between the young and old.
Description based on print version record.
Keywords: Intergenerational relations; Social justice